ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT FKS FOOD SEJAHTERA TBK PERIODE 2021-2023 - Nasyroh Hayati; Rory Handriano; Akhmad Julian Saputra (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
This study aims to Analyze Financial Reports in Measuring Financial Performance at PT Fks Food Sejahtera Tbk for the 2021-2023 Period. Research Method The method used in this study is a quantitative descriptive method which aims to determine the financial performance. The results of the study show that the liquidity ratio for the current ratio indicates that the company is not liquid. The quick ratio indicates that the company is in poor condition. The company's cash ratio is stated as illiquid. Profitability ratio analysis using Net Profit Margin, Return On Asset, and Return On Equity compared to the company's internal average shows that the company is making a profit. Solvency ratio analysis is measured using the debt to asset ratio indicating good conditions. The debt to equity ratio indicates good conditions and this company is solvable because the company has less debt than the capital or equity it has. Activity ratio analysis is measured using Fixed Asset Turnover and Total Asset Turnover has increased and decreased which indicates that the financial condition of the company is not good.